2018
DOI: 10.1111/nph.15281
|View full text |Cite
|
Sign up to set email alerts
|

The Hebeloma cylindrosporum HcPT2 Pi transporter plays a key role in ectomycorrhizal symbiosis

Abstract: Through a mutualistic relationship with woody plant roots, ectomycorrhizal fungi provide growth-limiting nutrients, including inorganic phosphate (Pi), to their host. Reciprocal trades occur at the Hartig net, which is the symbiotic interface of ectomycorrhizas where the two partners are symplasmically isolated. Fungal Pi must be exported to the symbiotic interface, but the proteins facilitating this transfer are unknown. In the present study, we combined transcriptomic, microscopy, whole plant physiology, X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 65 publications
7
35
0
Order By: Relevance
“…3). 6 Similar expression levels were observed in all tested conditions, indicating that external Pi availability did not affect the expression of HcPT1.2 in both axenic and symbiotic culture. Finally, we immunolocalized HcPT1.2 proteins in ectomycorrhizas produced on high and low P soil conditions using a recently detailed protocol.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…3). 6 Similar expression levels were observed in all tested conditions, indicating that external Pi availability did not affect the expression of HcPT1.2 in both axenic and symbiotic culture. Finally, we immunolocalized HcPT1.2 proteins in ectomycorrhizas produced on high and low P soil conditions using a recently detailed protocol.…”
supporting
confidence: 54%
“…More recently, we revealed that the second identified H + :Pi transporter of H. cylindrosporum, HcPT2, seems having a dual function in both Pi acquisition from the soil and Pi release towards the host cortical cells. 6 With the recent genome and transcriptome sequencing of H. cylindrosporum, 7-9 we also identified a third transporter that we named HcPT1.2 because of a higher level of similarity shared with HcPT1.1 (65.7 %) than with HcPT2 (48 %). Recently, an updated phylogenetic analysis of selected phosphorus transporter classes using the predicted proteins (https://jgi.doe.gov/JGI) of 35 fungal species, including 14 ECM ones, showed that both HcPT1.1 and HcPT1.2 proteins belong to the same subgroup (Ia) of H + :Pi transporter.…”
mentioning
confidence: 93%
“…HcPT2 expression was both weakly affected by Pi availability and upregulated in ectomycorrhizas. Furthermore, HcPT2 was located in hyphae of the Hartig net (Becquer et al, 2018). Therefore, the protein would fulfil many requirements of a Pi efflux carrier.…”
Section: Reviewmentioning
confidence: 99%
“…The finding that the silencing of GigmPT hampers the development of the fungus during symbiosis can be explained by a nutrient trade barrier, if the fungus cuts the phosphate supply (Schott et al ., ). Likewise, the proton‐coupled phosphate transporter HcPT2 from the fungus Hebeloma cylindrosporum has been shown recently to be important for the unloading of radiolabelled 32 Pi towards Pinus pinaster roots during this ectomycorrhizal association (Becquer et al ., ). The model predicts the existence of nutrient status‐dependent regulations of the different transporters. For example, it has been proposed previously that the plant sugar transporters should be regulated in response to the plant's intracellular phosphate level (Schott et al ., ).…”
Section: Discussionmentioning
confidence: 97%